Improving competitiveness for Caribbean development : report... (Ian Randle KingstonJM, 2003)
Addresses the supply side of development, and implicit in this is the assumption that the adjustments and reconstruction to be undertaken will be for the benefit of people. Focuses on the main challenges and opportunities arising out of the multilateral negotiations and the range of adjustment policies and actions that are needed.
Additional copy located in the office of the Secretary-General